Synergy Between Fiscal Decentralization and Regional Expenditure in Promoting Inclusive Economic Growth in Indonesia - Visca Apryansyah; Didit Purnomo (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the synergy between fiscal decentralization and regional expenditure in promoting inclusive economic growth in Indonesia. The research employs a quantitative approach using panel data covering 33 provinces over the period 2017–2022. The analysis is conducted using the Fixed Effects Model (FEM), selected based on the results of the Chow test and Hausman test. The findings indicate that fiscal decentralization, as well as intergovernmental transfers and village funds, do not have a significant effect on inclusive economic growth in Indonesia. In contrast, regional expenditure has a positive effect on inclusive economic growth. These results suggest that the effectiveness of regional fiscal policy is determined more by the quality and allocation of public spending rather than by the magnitude of fiscal authority or the amount of transfers received by regions. This study highlights the importance of strengthening governance and optimizing productive expenditure to promote inclusive economic development in Indonesia.